Effect of arginine vasopressin on the canine epicardial coronary artery: experiments on V1-receptor-mediated production of nitric oxide - Evora,Paulo Roberto B. (2003)
OBJECTIVE: To determine whether arginine vasopressin releases endothelium-derived nitric oxide (EDNO) from the epicardial coronary artery. METHODS: We studied segments of canine left circumflex coronary arteries suspended in organ chambers to measure isometric force. The coronary artery segments were contracted with prostaglandin F2alpha (2 x 10-6M) and exposed to a unique, strong arginine vasopressin concentration (10-6M) or titrated concentrations (10-9 a 10-5 M). RESULTS: The unique dose of arginine vasopressin concentration (10-6M) induced transient, but significant (p<0.05), relaxation in arterial segments with endothelium, and an increase, not significant, in tension in arteries without endothelium. Endothelium-dependent relaxation to arginine vasopressin was inhibited by Ng-monomethyl-L-arginine (L-NMMA, 10-5M) or N G-nitro-L-arginine (L-NOARG) (10-4M), 2 inhibitors of nitric oxide synthesis from L-arginine. Exogenous L-arginine (10-4M), but not D-arginine (10-4M), reversed the inhibitory effect of L-NMMA on vasopressin-mediated vasorelaxation. Endothelium dependent relaxation to vasopressin was also reversibly inhibited by the vasopressin V1-receptor blocker d(CH2)5Try(Me) arginine vasopressin (10-6M) (n=6, P<0.05). CONCLUSION: Vasopressin acts through V1 endothelial receptors to stimulate nitric oxide release from L-arginine.